Defeating Loss Mechanisms in 1D TiO2‐Based Hybrid Solar Cells. (18th March 2015) - Wisnet, A.; Bader, K.; Betzler, S. B.; Handloser, M.; Ehrenreich, P.; Pfadler, T.; Weickert, J.; Hartschuh, A.; Schmidt‐Mende, L.; Scheu, C.; Dorman, J. A.
<x xml:space="preserve">Abstract</x> Titanium dioxide (TiO2) semiconductors are widely used in energy conversion, energy storage, catalysis, and other electronic applications. Hydrothermally grown TiO2 nanowires are an alternative to mesoporous TiO2 nanostructures due to possible direct charge transport, but their full potential waits to be unleashed. Latest findings show a peculiar defect structure, consisting of small single‐crystalline fingers and free internal surfaces, which supposedly promote a number of loss mechanisms. In this paper, the influence of these defects on charge transport is studied on the basis of hybrid solar cells featuring a TiO2/dye/polymer interface. Electrical, optical, and structural characterization identifies a number of loss mechanisms, which are inhibited by the introduction of particular annealing steps at specific processing points during fabrication. An increase in power‐conversion efficiency of 35% is obtained, resulting in 2.71% and surpassing mesoporous films of the same material combination. These results suggest that caution has to be exercised when dealing with defect structures possibly present in metal oxides which appear single‐crystalline by conventional analysis methods.